Beautiful Dark Twisted Pedagogy: Kanye West and the Lessons of Participatory Culture - Garcia, Antero (Radical Teacher, 2013)
This article builds off of the author’s classroom experience as a high school teacher in South Central Los Angeles and looks at how cultural shifts with regards to media consumption and production impact liberatory pedagogical practice. Using media superstar Kanye West as a case study, this article argues that today’s classroom practices must expand in ways that reflect a more participatory culture. In particular, West’s marketing and engagement with his audience during the release of his 2010 album My Beautiful Dark Twisted Fantasy highlight how mainstream media practices offer pathways for renewing critical pedagogy in the 21st century.